2016
DOI: 10.1021/jacs.6b05574
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Coherence Times Enhancement in Vanadium(IV)-based Potential Molecular Qubits: the Key Role of the Vanadyl Moiety

Abstract: In the search for long-lived quantum coherence in spin systems, vanadium(IV) complexes have shown record phase memory times among molecular systems. When nuclear spin-free ligands are employed, vanadium(IV) complexes can show at low temperature sufficiently long quantum coherence times, Tm, to perform quantum operations, but their use in real devices operating at room temperature is still hampered by the rapid decrease of T1 caused by the efficient spin-phonon coupling. In this work we have investigated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
296
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(329 citation statements)
references
References 56 publications
33
296
0
Order By: Relevance
“…The systematically shorter T m times at all temperatures found for complex P2 as compared to P1 can be obviously related to a larger number of magnetic nuclei in the former complex that additionally contribute to the spectral diffusion mechanism of the electron spin dephasing. It is likely for this reason the T m times of both complexes measured by the primary spin echo appear shorter as in a number of other copper, vanadyl and chromium complexes reported and discussed in recent literature in the context of quantum information processing (see, e.g., [23,4548]). This has to be kept in mind while considering possible applications of Cu(II)–(bis)oxamato and Cu(II)–(bis)oxamidato complexes in molecular electronic devices.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The systematically shorter T m times at all temperatures found for complex P2 as compared to P1 can be obviously related to a larger number of magnetic nuclei in the former complex that additionally contribute to the spectral diffusion mechanism of the electron spin dephasing. It is likely for this reason the T m times of both complexes measured by the primary spin echo appear shorter as in a number of other copper, vanadyl and chromium complexes reported and discussed in recent literature in the context of quantum information processing (see, e.g., [23,4548]). This has to be kept in mind while considering possible applications of Cu(II)–(bis)oxamato and Cu(II)–(bis)oxamidato complexes in molecular electronic devices.…”
Section: Resultsmentioning
confidence: 90%
“…As a result, in addition to the CPMG echoes which are basically the refocused primary echo, other unwanted echoes appear. Complications due to a selective excitation of spins in CPMG ESR experiments were later observed in several works [4145]. However, up to now a detailed analysis of the underlying mechanisms giving rise to these complications, their impact on the determination of the spin dephasing time and the ways of elimination of unwanted effects were not elaborated sufficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by van Slageren and Sessoli's groups [60,61] have ascertained that the origin of the larger T M values (even at 300 K) observed for mononuclear V(IV) [21,22] and Cu(II) [16,18] complexes over those of {Cr 7 Ni} wheels is likely related to the coordination geometry and small spin-orbit coupling of the single metal ions in the former case, as well as the minimal contact of the magnetic orbital with the surrounding matrix, and the rigidity of the molecular structure. On the other hand, for the {Cr 7 Ni} wheels it has been found that the main source of decoherence is related to the electron-nuclear spin (hyperfine) coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the quantum states of this electron spins based system can be efficiently initialized with high thermal stability, representing a promising qubit. More recently, a new mononuclear V(IV) complex (Ph4P)2[VO(α-C3S5)2] 10 was reported, which enhances the quantum coherence by strong V=O double bond [47]. As shown in Figure 5a, the structure of 10 is similar to 4 except for the apical O atom.…”
Section: Introductionmentioning
confidence: 90%
“…Under a static magnetic field of 0.2 T, complex 4 displays slow magnetic relaxations below 10 K; while for complex 10, the temperature is raised up to 40 K. Their quantum coherences were detected by continuous-wave and pulsed EPR measurements on diluted samples. More recently, a new mononuclear V(IV) complex (Ph4P)2[VO(α-C3S5)2] 10 was reported, which enhances the quantum coherence by strong V=O double bond [47]. As shown in Figure 5a, the structure of 10 is similar to 4 except for the apical O atom.…”
Section: Introductionmentioning
confidence: 90%